The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1386/punk.7.3.317_1
|View full text |Cite
|
Sign up to set email alerts
|

Fan artefacts and doing it themselves: The home-made graphics of punk devotees

Abstract: Punk's embrace of autonomous, do-it-yourself, artistic production has been widely documented as a key element of the punk 'explosion'. At times, however, the rhetoric has exceeded the actual practice, and the boundary between DIY authorship and professional production has become blurred. Though much early punk visual material was indeed raw, rough and ready, and often appeared to run counter to any kind of formal aesthetic criteria in respect to design or taste, it was also widely the product of trained graphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Research shows how listening to or playing music can be beneficial for mood, cognition, and behavior, helping sufferers manage their physical and mental health, improve self-esteem and confidence, and build interpersonal relationships (McFerran and Saarikallio 2014; Rebecchini 2021). The growing fields of rock music studies and metal music studies have also identified similar benefits of music-related activities, whether playing in a band (Shadrack 2021), attending concerts (Hogan 2021), dressing in particular subcultural clothing (O’Hagan 2021), or making fanzines (Bestley and Burgess 2018). However, to date, little attention has been paid to online music fandoms and how these communities can serve as a positive environment for mental health and well-being (with the exception of Quinn 2019).…”
Section: January 4 2021mentioning
confidence: 99%
“…Research shows how listening to or playing music can be beneficial for mood, cognition, and behavior, helping sufferers manage their physical and mental health, improve self-esteem and confidence, and build interpersonal relationships (McFerran and Saarikallio 2014; Rebecchini 2021). The growing fields of rock music studies and metal music studies have also identified similar benefits of music-related activities, whether playing in a band (Shadrack 2021), attending concerts (Hogan 2021), dressing in particular subcultural clothing (O’Hagan 2021), or making fanzines (Bestley and Burgess 2018). However, to date, little attention has been paid to online music fandoms and how these communities can serve as a positive environment for mental health and well-being (with the exception of Quinn 2019).…”
Section: January 4 2021mentioning
confidence: 99%
“…Punk clothes … display[ed] a tension between the punk high fashion of Vivienne Westwood … and the charity shop adaptations and home-made, do-it-yourself outfits of many early fans. (Bestley and Burgess, 2018: 318)…”
Section: Challenging the Diy/punk Nexusmentioning
confidence: 99%
“…Punk was not a particularly participatory (live) music, as has been recognised by Bestley and Burgess: while punk claimed to be a project of ‘participation and the levelling of hierarchies between performer and audience, … in practice such hierarchies were harder to budge’ (2018: 318). Setting aside perhaps events such as the legendary (which may mean misrepresented) Sex Pistols Manchester gigs at the Lesser Free Trade Hall in the summer of 1976, in which many of the young Mancunians and Salfordians present would go on to carve notable musical careers (see Morley, 2011), the live music space of a punk club or gig was a largely conventionally organised one, with a small number of producers in a designated elevated space (bands on stage), being watched by paying consumers (the crowd).…”
Section: Challenging the Diy/punk Nexusmentioning
confidence: 99%
“…By the end of 1975, British punk scene-leaders the Sex Pistols were developing their own punk visual style. During the early part of 1976, Helen Wellington-Lloyd designed the first Sex Pistols logo and created a number of early gig flyers for the band, frequently using type cut out from tabloid newspapers, felt pens, and Letraset (a dry transfer, rub-down lettering system used by designers to set small amounts of type) to create a hard-hitting visual aesthetic (see Bestley and Burgess 2018). Jamie Reid began working directly with manager Malcolm McLaren and the band in the summer of 1976, and developed the aes thetic further over the following year.…”
Section: A New Wave: the New Punk Designersmentioning
confidence: 99%